Constitutional Federalism, Individual Liberty, and the Securities Litigation Uniform Standards Act of 1998 - A. C. Pritchard (Washington University Law Quarterly, 2000)
Part I provides background on the historical development of constitutional federalism, the Supreme Court’s decisions in this area, and the apparent demise of constitutional limits on federal power. Part II then reviews the Court’s revival of constitutional federalism over the last decade. Part III focuses on the Court’s decisions applying the principles of constitutional federalism to state courts. Part IV provides background to Congress’s enactment of the Uniform Act and explains why it adopted the form of preemption that it did.
Keywords: Exclusive & amp; concurrent legislative powers; Securities fraud; Class actions (Civil procedure); Federal government; Federalism; Preemption (Legislative power); Securities Litigation Uniform Standards Act of 1998